2021
DOI: 10.1111/tbed.14172
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of porcine circovirus 4 in Henan Province of China: A retrospective study from 2011 to 2021

Abstract: Porcine circovirus 4 (PCV4), a novel circovirus, was first discovered in April 2019 in Hunan Province of China. At present, PCV4 infection has been detected in China and South Korea. However, until 2019, there was little information about its circulating status and genetic characteristics. To further clarify the origin and prevalence of PCV4, a total of 152 clinical samples collected from 49 different swine farms of 15 cities in Henan Province of China from 2011 to 2021 were tested for the presence of PCV4 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…At present, according to research reports, PCV4 has been detected in Hunan, Guangxi, Shaanxi, Henan and Inner Mongolia provinces of China ( 3 , 6 , 13 , 14 , 20 ). This is the first study to report the successful detection of PCV4 in the Sichuan province.…”
Section: Discussionmentioning
confidence: 99%
“…At present, according to research reports, PCV4 has been detected in Hunan, Guangxi, Shaanxi, Henan and Inner Mongolia provinces of China ( 3 , 6 , 13 , 14 , 20 ). This is the first study to report the successful detection of PCV4 in the Sichuan province.…”
Section: Discussionmentioning
confidence: 99%
“…Although PCV4 was discovered in 2019 in the Hunan province of China, retrospective studies demonstrated that PCV4 DNA was present in swine samples collected in 2012 [ 4 ], implying PCV4 has been circulating in pigs for at least a decade. Since 2019, PCV4 has been reported in several provinces of China, including Hunan, Henan, Jiangsu, Anhui, Shanxi, Guangxi, and Inner Mongolia [ 3 , 4 , 10 14 ]. Furthermore, PCV4 was also detected in domestic swine in Korea [ 15 , 16 ].…”
Section: Evolution and Genetic Diversity Of Pcv4mentioning
confidence: 99%
“…PCV4 was detected in pigs of various age groups and in several tissues, as co-infections with other pathogens, and with a variety of clinical signs, as summarized in Table 1 . To date, PCV4 genomic DNA has been detected in pigs in several provinces in China, as well as in South Korea, with positive rates ranging from 1.6 to 45.39% [ 4 , 10 ]. PCV4 can infect almost all ages of pigs, including sucking, weanling, and fattening pigs, as well as sows and fetuses [ 4 , 10 , 11 , 15 ].…”
Section: Epidemiology Of Pcv4 and Clinical Diseases Associated With T...mentioning
confidence: 99%
See 2 more Smart Citations